PENERAPAN MEDIA PEMBELAJARAN BIANGLALA PADA PEMBELAJARAN MATEMATIKA KELAS III SD NEGERI 4 SRIKATON - Rini Anggraini; Idul Adha; Andriana Sofiarini (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2022)
This study aims to determine the mathematics learning outcomes of third grade students of SD Negeri 4 Srikaton after the Ferris wheel media was significantly completed and active. The research conducted here is experimental research in the form of one group pre-test and post-test design. This research was conducted at SD Negeri 4 Srikaton. The population and sample used in this study were Grade III students at SD Negeri 4 Srikaton, here the researcher used a saturated sampling technique where in this sample all members of the population were used as samples. In collecting the data needed, the writer uses test techniques in the form of questions, and observations. With the calculation results obtained z (count) (15.24) > z_table (1.64), so in this case Ho is rejected and Ha is accepted. Therefore, the hypothesis proposed in this study can be accepted as true, meaning that the Ferris wheel learning media can complete learning outcomes and increase student activity in mathematics learning for class III SD Negeri 4 Srikaton.